STUDI KELAYAKAN BISNIS PADA PRODUK SEAFOOD SITUBONDO - Kurniawan, Aldy; Fandiyanto, Randika; Miftahul, Rozikin (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Seafood Situbondo is a food restaurant that serves a variety of fresh seafood and is the first in Situbondo which is located on Jalan Merak No 1 Kel.Patokan, Situbondo, East Java. This restaurant also has Live Sea Water Lobster in the middle of Situbondo City. The restaurant's contemporary and aesthetic concept is very different from the others, not only seafood but also fried rice noodles and other menus. So this restaurant is very suitable for the taste buds of seafood lovers. This type of research is qualitative research using phenomenology as a method and technique for collecting data based on observations, interviews with Situbondo seafood owners and documentation.